The making of feudal agricultures? - Barceló, Miquel; Sigaut, François. (Leiden ; Boston : Brill, 2004)
Was there a discernible set of changes in the techniques of arable farming, animal husbandry and their associated technologies at the end of antiquity which marked a clear break with an established 'ancient world economy' and ushered in the 'new agricultures' of the early middle ages? Were such changes not already visible in antiquity? And what was the impact of political, economic, social and environmental change in these processes? The 6 papers in this volume reject simple evolutionary models charting progress from "protohistory" to the "Roman period" to the "Dark Ages" to the "Middle Ages" and insisted rather on the notion of inheritance, so that the farming economy laid down in protohistoric times continued to exist during the early Middle Ages. The collapse of a capitalistic commercial economy of the later Roman Empire though accompanied by political and military crises did not entail a regression of the farming economy. The growth in farming in the 8th - 9th C, resting on a demographic increase combined with intensive land clearance episodes, owed much to the preceding centuries: the change resides more in an intensification than in the introduction of new features. With contributions by Pascal Reigniez, Catherine Rommelaere, Georges Raepsaet, G. Comet, Aline Durand and Philippe Leveau.
L'evolution des techniques / Francois Sigaut -- Histoire et techniques: l'outil agricole dans la periode du haut Moyen-Age (V[superscript e]-X[superscript e] siecle) / Pascal Reigniez -- Les techniques de traction animale. De l'Antiquite au Moyen Age / Catherine Rommelaere and Georges Raepsaet -- Les cereales du bas-Empire au Moyen Age / Georges Comet -- Farming in mediterranean France and rural settlement in the late roman and early medieval periods: the contribution from archaeology and environmental sciences in the last twenty years (1980-2000) / Aline Durand and Philippe Leveau -- Missing Water-Mill: A question of technological diffusion in the High Middle Ages / Miquel Barcelo.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Agriculture -- Europe, Western -- History; Agricultural innovations -- Europe, Western -- History; Middle Ages; Agriculture -- Europe de l'Ouest -- Histoire; Agriculture -- Innovations -- Europe de l'Ouest -- Histoire; Moyen Âge.; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- Crop Science; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- General; Agricultural innovations; Agriculture; Middle Ages; Western Europe; Nutztiere; Kulturpflanzen; Landwirtschaft; Landwirtschaftliches Gerät; Landbouw; Vernieuwing; History